Persaingan Melalui e-Marketing - Slamet, Giarti (Responsibilitas, 2011)
Abstract E-Marketing is the marketing side of the E-Commerce, which consists of companies working to communicate something, promote, and sell goods and services over the internet. At this time the Internet so close to us, then we need to shift toward the rhetoric about the Internet industry, e-business strategy and the new economy as well as to what the internet is required. It is a versatile technology, with a full set of tools the ability to function, whether or not, in some industries, and many became part of the various strategies. The development of e-business and e-commerce in the future is predicted to be accelerated in line with the growth of telephone networks, including TV set-up box, wireless applications and broadband access. E-Marketing is the marketing side of the E-Commerce, which consists of companies working to communicate something, promote, and sell goods and services over the internet. Key words: Internet, E-Commerce, and E-Marketing